Advance of genetics in multiple sclerosis. (December 2015) - Matsushita, Takuya
Abstract: Multiple sclerosis (MS) is characterized by temporal and spatial dissemination of demyelination in the central nervous system and the pathogenesis results from both genetic and environmental factors. Elaborate surveys have revealed familial accumulation of MS and provide unequivocal evidence that genetic factors contribute to the susceptibility. Family studies strongly suggest a polygenic model of inheritance explained by relatively common allelic variants. The major histocompatibility complex (MHC) in chromosome 6p21.3 has been identified as a genetic risk locus for MS from 1970s, but it was not until genome wide association studies (GWAS) were conducted in MS that genetic risks outside of MHC were identified. International collaboration and the development of new laboratory and analytical methods enabled detection of risk loci with comparably low effect size. Currently, more than 100 risk loci outside of MHC were identified. However, the heritability is not fully explained by the genetic risks that have been identified by GWAS. The knowledge of genetic effects on clinical phenotype is also incomplete.